RNS60 exerts therapeutic effects in the SOD1 ALS mouse model through protective glia and peripheral nerve rescue - Antonio Vallarola; Francesca Sironi; Massimo Tortarolo; Noemi Gatto; Roberta De Gioia; Laura Pasetto; Massimiliano De Paola; Alessandro Mariani; Supurna Ghosh; Richard Watson; Andreas Kalmes; Valentina Bonetto; et al. (Journal of Neuroinflammation, 2018)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects the motor neuromuscular system leading to complete paralysis and premature death. The multifactorial nature of ALS that involves both cell-autonomous and non-cell-autonomous processes contributes to the lack of effective therapies, usually targeted to a single pathogenic mechanism. RNS60, an experimental drug containing oxygenated nanobubbles generated by modified Taylor-Couette-Poiseuille flow with elevated oxygen pressure, has shown anti-inflammatory and neuroprotective properties in different experimental paradigms. Since RNS60 interferes with multiple cellular mechanisms known to be involved in ALS pathology, we evaluated its effect in in vitro and in vivo models of ALS. Methods Co-cultures of primary microglia/spinal neurons exposed to LPS and astrocytes/spinal neurons from SOD1G93A mice were used to examine the effect of RNS60 or normal saline (NS) on the selective motor neuron degeneration. Transgenic SOD1G93A mice were treated with RNS60 or NS (300 μl/mouse intraperitoneally every other day) starting at the disease onset and examined for disease progression as well as pathological and biochemical alterations. Results RNS60 protected motor neurons in in vitro paradigms and slowed the disease progression of C57BL/6-SOD1G93A mice through a significant protection of spinal motor neurons and neuromuscular junctions. This was mediated by the (i) activation of an antioxidant response and generation of an anti-inflammatory environment in the spinal cord; (ii) activation of the PI3K-Akt pro-survival pathway in the spinal cord and sciatic nerves; (iii) reduced demyelination of the sciatic nerves; and (iv) elevation of peripheral CD4+/Foxp3+ T regulatory cell numbers. RNS60 did not show the same effects in 129Sv-SOD1G93A mice, which are unable to activate a protective immune response. Conclusion RNS60 demonstrated significant therapeutic efficacy in C57BL/6-SOD1G93A mice by virtue of its effects on multiple disease mechanisms in motor neurons, glial cells, and peripheral immune cells. These findings, together with the excellent clinical safety profile, make RNS60 a promising candidate for ALS therapy and support further studies to unravel its molecular mechanism of action. In addition, the differences in efficacy of RNS60 in SOD1G93A mice of different strains may be relevant for identifying potential markers to predict efficacy in clinical trials.